Development of a culturally adaptable internet-based cognitive behavioral therapy for Japanese women with bulimia nervosa - Hamatani, Sayo; Matsumoto, Kazuki; Ishibashi, Tomoaki; Shibukawa, Ryunosuke; Honda, Yuki; Kosaka, Hirotaka; Mizuno, Yoshifumi; Andersson, Gerhard (Frontiers in Psychiatry, 2022)
Background: The process of cultural adaptation of internet-based cognitive behavioral therapy (ICBT) programs for bulimia nervosa (BN) have rarely been reported despite the potential influence of cultural adaptation of psychosocial interventions on therapeutic response. Aim: This study aimed to illustrate development process of an ICBT program for Japanese women with bulimia nervosa (BN). Methods: A mixed methods approach was used to assess cultural adaptation of the prototype of an original ICBT program by using the Cultural Relevance Questionnaire (CRQ). Five women with BN and seven clinicians were interviewed using the CRQ. Results: Quantitative analyses were conducted to assess cultural adaptation of the prototype of the program and participants rated cultural adaptation as high. A qualitative analysis of the mixed method supported the culturally sensitive changes implemented. Conclusions: The results of this study show that a series of processes can make ICBT programs more culturally adapted.